CDIO and the Engineering of Personalised Learning Environment: An Exploration - M.M, Raihanah; Arsad, Norhana; Muzhafar Idrus, Mohd (International Journal of Engineering and Technology, 2019)
One of the fourteen grand challenges for engineering in this century, as identified by the National Academy of Engineers (USA) in 2008, is the advancement of personalised learning. The relevance of creating personalised learning in the context of Malaysian higher education can be inferred among the ten shifts stated in the Malaysian Education Blueprint 2015â€“2025 (Higher Education), which feature key elements towards spurring excellence in the nationâ€™s higher education. This research investigates the spaces and opportunities available in a Personalized Learning Environment (PLE) for enhancing learnersâ€™ soft skills beyond course content. How is this policy transferred into practice? Specifically, how can educators use technology to engineer a holistic personalised learning experience? In the context of 21st century education, how can we ensure that learnersâ€™ soft skills are given due attention in the PLE? Using key concepts in engineering education, primarily Conceive-Develop-Implement-Operate (CDIO), and the fundamentals of disruptive innovation, this study illustrates the engineering process adopted to design and implement a PLE in the humanities. As findings illustrate, comprehensive PLE management creates opportunities for enhanced learner autonomy and leadership development while ensuring that the educatorâ€™s roles continue to be relevant and evident. Â